AKTIVITAS SITOTOKSIK HASIL PARTISI ETIL ASETAT EKSTRAK PETROLEUM ETER DAN EKSTRAK METANOL DAUN KAYU APU (Pistiae Folium) - Sentot Joko Raharjo; Rahayu Wahyu Ningsih (Faculty of Pharmacy, Universitas Gadjah Mada, 2015)
This study aims to explore the cytotoxic test (LC50) towards Artemia salina L. larvae of the partition ethyl acetate fractions from methanol extracts and petroleum ether (PE) extracts of Pistiae folium. The leaves of Pistiae folium was extracted using solvents soxhletation with methanol solvent and petroleum ether solvent. Both extracts successively partitioned with n-hexane and ethyl acetate, respectively. Identification of secondary metabolites was using phytochemical screening method and TLC (Thin Layer Chromatography). TLC analysis was using the eluent chloroform: methanol 3: 1 by citroboric acid spot analysis. The cytotoxic activity was using Brine Shrimp Lethality Test (BSLT) method. The result of partition from methanol extracts was 6.25% and from PE extracts was 0.69%. The phytochemical screening test showed that it contained flavonoids, saponins and steroids. The TLC analysis identified flavonoid compounds. The cytotoxic activity (LC50) of the ethyl acetate partition from methanol extracts and petroleum ether extracts of Pistiae folium were 79.9298mg/mL and 51.7608mg/mL, respectively. The result showed that the cytotoxic activity of ethyl acetate fractions partitined from methanol extract of Pistiae folium was higher than the PE extracts.